Psychological impact of COVID-19 on teens belonging to a social media group - Geethika Sai, K; Jalaja, Ramesh; Amutha, Anandakumar; Venkatesan, U; Anjana, Ranjit; Unnikrishnan, Ranjit (Journal of diabetology, 2021)
Aims: To evaluate the psychological impact of COVID-19 on teens in a small WhatsApp group from Chennai. Materials and Methods: The study population comprised of teenagers, aged 12 to 20 years, who belong to a WhatsApp group. The questions were framed and developed based on the transitional impact scale which has high test-retest reliability. Through the WhatsAppgroup, the teens were informed about the survey. Those who were willing to participate were provided the website link to fill the questionnaire. Fisher's exact tests were used to assess differences in proportions wherever applicable. Results: Among the 320 participants, 16.7% of them were boys and 83.3% were girls, and the mean age of boys and girls was 16.2 ± 2.1years and 15.6 ± 1.8 years, respectively. More than 40% of teens expressed that they often felt stressed out. Teens of both the genders reported getting irritated by small normal things (34.1%), thought they were helpless (32.8%), sometimes they felt like a burden to people around them (27.8%), and 36.9% reported feeling lonely or left out often. Regarding usage of electronic devices, 47.7% of girls and 58.5% of boys were always on any one of the electronic devices like mobiles, tabs, laptops, television, etc. Similarly, more than 50% of the boys and 60% of the girls slept 6-8h during this pandemic situation. Conclusion: This study shows that this life-changing transitional event has made a massive impact on the daily routine of these teenagers. Parents, health care professionals, and educators have to make sure that the teens come to terms with the current realities of the situation and to make use of the government support programs.